The grip book : the studio grip's essential guide - Uva, Michael (Routledge, Taylor & Francis Group, 2018)
"Gain the essential skills of a professional grip to become the jack and master of all trades on any movie or television show set. Discover vital insider tips ranging from how to operate cutting-edge rigging and lighting equipment to performing difficult camera mounts on aircraft, boats, trains, and cars. In The Grip Book, seasoned Hollywood grip Michael G. Uva teaches you to install, set up, maintain, and ensure the safety of all equipment on a set, such as C-stands, cameras, and any specialty gear needed for a shoot. Guidelines for on-set etiquette and how to succeed as a technical crew member will jumpstart your career and make you a valuable asset on any film or television crew. This new 6th edition marks the books 30th anniversary and has been fully revised and updated to include expanded coverage of on-set scenarios, such as gripping near water and at heights; a brand-new chapter dedicated to providing insider solutions to various gripping problems that can often appear insurmountable to the uninitiated; and a brand-new companion website featuring a downloadable reference guide on grip equipment, and extensive how-to video demonstrations. Other features include technical expertise on maintaining the latest and greatest filmmaking equipment; an updated self-test section containing over one hundred questions and answers; a comprehensive appendix containing a robust glossary of insider and equipment terms; and guidelines on what a grip has to be physically able to perform in their day-to-day duties."--Provided by publisher.